Stochastic Multi-mode Resource-constrained Project Scheduling Problem Under Resource Calendar And Risk-net Present Value. - Zhang, Qian (2024)
Due to the uncertainty phenomenon, the stochastic multi-mode resource-constrained project scheduling problem (SM-RCPSP) has become a significant research problem. SM-RCPSP is scheduling activities with multiple execution modes under resource supply and activity priority relationship constraints in the stochastic environment based on non-linear programming theory and multi-objective programming theory. The first objective of this thesis is to build a Time-Cost Trade-off Model for SM-RCPSP under a fixed resource calendar by minimizing the project completion time and cost. Assuming that the activity duration is the stochastic variable, a Time-Cost Trade-off Model is constructed under the fixed resource calendar, resource supply, execution mode, and priority relationship constraints. The second objective of this thesis is to build a Markov Chain Model for SM-RCPSP under a stochastic resource calendar by minimizing the project completion time and cost. Assuming that the activity duration is the stochastic variable and the Markov chain is used to describe the stochastic resource calendar, a Markov Chain Model is constructed under the stochastic resource calendar, resource supply, execution mode, and priority relationship constraints. The third objective of this thesis is to build a risk-net present value trade-off model for SM-RCPSP by minimizing the project condition net present value at risk and maximizing NPV. Assuming that the activity duration and cash flow are stochastic variables, a Risk-NPV Trade-off Model is constructed under resource supply, execution mode, priority relationship, and deadline constraints.